Identifikasi Faktor Risiko Stunting pada Balita: Studi di Wilayah Kerja Puskesmas Aek Godang, Padang Lawas Utara - Herawati Harahap; Usrawati Pasaribu; Rika Apripan; Sri Juwarni (Pusat riset dan Inovasi Nasional, 2025)
Stunting is a condition of growth failure in toddlers due to chronic malnutrition that occurs over a long period of time, especially in the first 1,000 days of life. Several major risk factors for stunting that are often found in Posyandu include the nutritional status of pregnant women, parenting patterns, exclusive breastfeeding, and environmental sanitation. To analyze the Identification of Risk Factors for Stunting in Toddlers: A Study in the Working Area of ​​the Aek Godang Health Center, North Padang Lawas. The type of observational study with a cross-sectional design, the study population was 139 people. This study used samples from all mothers who had stunted toddlers in Hulu Sihapas District, North Padang Lawas Regency, with the total sampling method. Data collection used a research questionnaire. Data were analyzed univariately, bivariate (chi-square), and multivariate (logistic regression) with the enter method. Newborn weight (p = 0.001) and healthy toilets (p = 0.001) significantly influenced the risk of stunting, with low birth weight and poor sanitation increasing the risk of growth disorders in toddlers. This study shows that newborn weight (p = 0.001) and healthy toilets (p = 0.001) have a significant effect on the risk of stunting in toddlers. Babies with low birth weight and environments with poor sanitation increase the likelihood of stunting. More attention is needed to monitor newborn weight and increase access to healthy latrines to reduce the prevalence of stunting. The government and health workers are expected to strengthen nutrition and sanitation programs at the community level.